ANALISIS KINERJA DAN PARTISIPASI ANGGOTA KOPERASI MANDIRI JAYA KABUPATEN BOGOR - Fajrin Rimadhyani Firdaus; Lukman Mohammad Baga (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2019)
Cooperative is one of many institutions that support agribusiness sector in rural area. It has big role in agricultural sector because of Indonesia’s farming system characterized by small scale and scattered business. The purpose of this research is to analyze the level of institutional performance and member participations as well as to analyze strategies to improve the performance of Mandiri Jaya Cooperative. Data obtained from 30 respondents with purposive sampling method. This research analyzed by Development Ladder Assesment (DLA) and Rank Spearman Correlation Test. The result shows that the cooperative’s performance was in green zone which means this cooperative was in good condition. Rank Spearman Correlation Test shows that there is a straight line relationship between social economic benefit with the member participation level in the cooperative’s organizational, capital and business activity. Some policies can be applied to increase the role of the Mandiri Jaya Cooperative to become an institution which not only helps resolve member capital issues. Things that can be done such as providing education and basic understanding of cooperative identity, strengthening internal management conditions, and strengthening networks to create partnerships that can support cooperative’s performance.